Use of telephone calls to manage glycemic control at Mexico’s northern border - Vázquez Martínez, Víctor Hugo; Martínez Bautista, Humberto; Loera Morales, Jesús; Garzón Garcia, Francisco Daniel; Vélez Maldonado, David; Muñoz Villegas, Patricia (Frontiers in Endocrinology, 2025)
IntroductionTelephone calls were used for glycemic control in type 2 diabetes mellitus (T2DM) patients during the Covid-19 pandemic. The study’s objective was to determine the factors that favor glycemic control in patients with T2DM using telephone calls in the Mexico’s northern border.MethodsA retrospective cohort study was conducted with T2DM patients from the Family Medicine Unit 33 in Reynosa, Tamaulipas, from June 2021 to June 2022. The evaluation of glycemic control involved measuring glycated hemoglobin at the beginning and end of telephone follow-up. Clinical, demographic, social, and laboratory factors were analyzed using univariate and bivariate statistical methods to compare initial and final glycemic control, finally, two logistic regression models were estimated considering glycemic control as a binary variable.ResultsA total of 287 participants were followed up, comprising 122 men and 165 women, where 71.78% received nine or more phone calls. Initially, 49.13% had glycemic control, but by the end of the follow-up, it increased by 7%. Females show an Odds Ratio (OR) of 0.475 (95% CI 0.269-0.838), high-density lipid levels with an OR = 0.982 (p=0.078), and 11 follow-up telephone calls with an OR = 0.403 (95% CI 0.165-0.985), which represented factors contributing to glycemic control. Poor glycemic control is more likely in individuals with a high cardiovascular risk, with an OR of 2.193 (p=0.085).ConclusionCell phone calls can effectively control glycemia in T2DM patients. Therefore, they can be used as a substitute for in-person medical care.